Efek Pasta Gigi Non Detergen pada Gingivitis dan Stomatitis Aphtosa Pemakai Alat Cekat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The rising of orthodontic care technique had been followed by modern and competitive orthodontic equipment. This orthodontic equipments had been manufactured comfortly so it should be aestetic and still keep the oral hygiene. The orthodontic observed conclude that the used of each fixed appliance orthodontic in early stage followed by soft tissue inflamation. Gingivitis and aphtosa stomatitis were routinely found and fixed appliance orthodontic used. Gingivitis in orthodontic equipment user caused by over plaque in the orthodontic equipment space, that causes bacteria multiply excessive. The power of orthodontic equipment will change periodontal tissue structure that cause gingivitis at the beginning then become periodontitis. Aphtosa stomatitis is lesion in oral cavity that due to trauma and irritation by orthodontic equipment. The both situation can be excelled by making oral cavity ecology equally. Quality and quantity of saliva must be keeping. Dry mouth must be handled for not making worse the condition. The 0 % detergent toothpaste will help balance oral cavity ecology and reduce gingivitis and aphtosa stomatitis on fixed orthodontic equipment user